Ability of Football Players Asesment; A Literature Review on Scopus Indexed Journals - Yudhi Purnama; Tandiyo Rahayu; Taufik Hidayah; Sudjatmiko Sudjatmiko (International Conference on Science, Education, and Technology, 2023)
Every soccer team wants to achieve the highest in their respective league. One of his top achievements is having a very reliable soccer player. Players must have the ability to play football in all aspects, both physical, mental, abilities, skills and tactics. This study aims to find out what assessments are made of a soccer player by summarizing several Scopus indexed articles. The method used in this study is a systematic literature review. Search range for articles in 2017-2023. The keywords used are "instruments" OR "instruments" AND "assessment" AND "ability" OR "performance" AND "soccer" OR "football". The results of the literature show that there are several types of assessments carried out to determine the skills of a soccer player, including: endurance, speed, muscle strength, agility, coordination, balance, passing, shooting and dribbling the ball. The conclusion in this study is to know good physical condition and good football playing skills, soccer players must carry out valid and reliable assessment to get accurate results.